2014
DOI: 10.1016/j.jjcc.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of adaptive servo-ventilation in patients with severe systolic heart failure

Abstract: Our study demonstrated that ASV therapy is safe and effective for use in very severe systolic HF patients as well as in relatively mild systolic HF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…11- 17 Patients with LV reverse remodeling have a very favorable prognosis as compared with patients who do not. 18 The present study was conducted as a multicenter, randomized, controlled study in order to examine the superiority of the ASV group to the control group regarding the cardiac function-improving and LV remodeling-inducing effects of ASV therapy that SAVIOR-R 14 had suggested.…”
mentioning
confidence: 99%
“…11- 17 Patients with LV reverse remodeling have a very favorable prognosis as compared with patients who do not. 18 The present study was conducted as a multicenter, randomized, controlled study in order to examine the superiority of the ASV group to the control group regarding the cardiac function-improving and LV remodeling-inducing effects of ASV therapy that SAVIOR-R 14 had suggested.…”
mentioning
confidence: 99%
“…Furthermore, many reports showed that the ASV therapy for the patients with HF was effective. 5,7,9,10,11,[18][19][20][21][22] Although it is well known that the prognosis of patients is negatively correlated with the severity of SDB, 12 little has been reported on the long-term prognosis in patients with HF after initiating ASV therapy. Earlier, we showed that ASV therapy was effective for patients with HF and that it improved their prognosis after one year.…”
Section: Findings and Data Interpretationmentioning
confidence: 99%
“…9 Similarly, other reports suggested that the ASV therapy improved the LVEF, BNP, and the prognosis of patients with HF. 6,10,11 However, previous reports have suggested that there is a negative relationship between the severity of SDB and prognosis. 1,12 It remained unclear as to whether ASV could improve the long-term prognosis of patients with HF, regardless of the severity of SDB.…”
Section: Introductionmentioning
confidence: 99%
“…This treatment was originally developed to treat sleep-disordered breathing (SDB), but has been widely indicated for the treatment of moderate to advanced heart failure (HF) even in the absence of SDB. [2][3][4][5][6][7][8][9][10][11][12][13][14] Cowie, et al recently demonstrated an increased mortality in patients receiving aggressive ASV therapy for HF and central sleep apnea compared with the control group. 15) Another Japanese prospective randomized controlled study did not show an obvious advantage of ASV therapy over optimal medical therapy.…”
mentioning
confidence: 99%